Cellular uptake and localization of inhaled gold nanoparticles in lungs of mice with chronic obstructive pulmonary disease - Geiser, Marianne; Quaile, Oliver; Wenk, Alexander; Wigge, Christoph; Eigeldinger-Berthou, Sylvie; Hirn, Stephanie; Schäffler, Martin; Schleh, Carsten; Möller, Winfried; Mall, Marcus A.; Kreyling, Wolfgang G. (Particle and fibre toxicology, 2013)
Inhalative nanocarriers for local or systemic therapy are promising. Gold nanoparticles (AuNP) have been widely considered as candidate material. Knowledge about their interaction with the lungs is required, foremost their uptake by surface macrophages and epithelial cells.
Gesehen am 18.03.2021